2021
DOI: 10.1016/j.jaci.2020.12.657
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between IFN-γ and TWEAK through miR-149 amplifies skin inflammation in psoriasis

Abstract: Background: Psoriasis is a chronic inflammatory skin disease with disturbed interplay between immune cells and keratinocytes. A strong IFN-g signature is characteristic for psoriasis skin, but the role of IFN-g has been elusive. MicroRNAs are short RNAs regulating gene expression. Objective: Our aim was to investigate the role of miR-149 in psoriasis and in the inflammatory responses of keratinocytes. Methods: miR-149 expression was measured by quantitative RT-PCR in keratinocytes isolated from healthy skin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…In the present study, we found that the expression of TWEAK, activin A, and persephin was upregulated after Homer1 protein treatment. TWEAK, which is commonly involved in immune regulation, inflammation, and apoptotic processes, is a member of the TNF superfamily of cytokines [ 46 , 47 ] and it has been shown that crosstalk between IFN-γ and TWEAK amplifies skin inflammation in psoriasis through miR-149 [ 48 ]. Activin A is believed to be a pleiotropic cytokine with pro-inflammatory and anti-inflammatory properties [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the expression of TWEAK, activin A, and persephin was upregulated after Homer1 protein treatment. TWEAK, which is commonly involved in immune regulation, inflammation, and apoptotic processes, is a member of the TNF superfamily of cytokines [ 46 , 47 ] and it has been shown that crosstalk between IFN-γ and TWEAK amplifies skin inflammation in psoriasis through miR-149 [ 48 ]. Activin A is believed to be a pleiotropic cytokine with pro-inflammatory and anti-inflammatory properties [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the increased MAPK and NF-κB activation promote epidermal hyperproliferation and exacerbate psoriatic pathogenesis by triggering inflammatory responses [4,33,34]. Particularly, p38 MAPK over-phosphorylation breaks down the homeostasis of skin and induces cellular stresses, which might be the trigger of psoriasis dermatitis [35,36]. NF-κB, indicated by the p65 subunit nuclear translocation and phosphorylation as well as the IκBζ ablation, is the key component of IL-17 mediated skin inflammation [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This may result from elevated proinflammatory cytokines in psoriasis-TNF, IL-17, IL-1 and IL-6, which are known to inhibit melanogenesis and specifically PKA, MITF, TYR and DCT [ 12 , 14 , 30 ]. Likewise, another inflammatory cytokine associated with psoriasis, interferon gamma, has been shown to suppress CREB, MITF, p38 MAPK and melanogenesis [ 31 , 32 , 33 ]. These current findings are in agreement with our previous study where we found lowered expression of TYR and TYRP1 mRNA in psoriatic skin compared to healthy controls [ 16 ].…”
Section: Discussionmentioning
confidence: 99%